Brown Adipose Tissue and Skeletal Muscle 18F-FDG Activity After a Personalized Cold Exposure Is Not Associated With Cold-Induced Thermogenesis and Nutrient Oxidation Rates in Young Healthy Adults - Sanchez-Delgado, Guillermo; Martinez-Tellez, Borja; Garcia-Rivero, Yolanda; Alcantara, Juan M. A.; Acosta, Francisco M.; Amaro-Gahete, Francisco J.; Llamas-Elvira, Jose M.; Ruiz, Jonatan R. (Frontiers in Physiology, 2018)
Cold induced thermogenesis (CIT) in humans results mainly from the combination of both brown adipose tissue (BAT) and skeletal muscle thermogenic activity. The relative contribution of both tissues to CIT and to cold induced nutrient oxidation rates (CI-NUTox) remains, however, to be elucidated. We investigated the association of BAT and skeletal muscle 18F-FDG activity after a personalized cold exposure with CIT and CI-NUTox in 57 healthy adults (23.0±2.4 years old; 25.1±4.6 kg/m2; 35 women). BAT and skeletal muscle (paracervical, sternocleidomastoid, scalene, longus colli, trapezius, parathoracic, supraspinatus, subscapular, deltoid, pectoralis major, and triceps brachii) metabolic activity were assessed by means of a 18Fluorodeoxyglucose positron emission tomography-computed tomography scan preceded by a personalized cold exposure. The cold exposure consisted in remaining in a mild cold room for 2 hours at 19.5-20ºC wearing a water perfused cooling vest set 3.8ºC above the individual shivering threshold. On a separate day, we estimated CIT and CI-NUTox by indirect calorimetry under fasting conditions for one hour of personalized cold exposure. There was no association of BAT volume or activity with CIT or CI-NUTox (all P>0.2). Similarly, the skeletal muscle metabolic activity was not associated either with CIT or CI-NUTox (all P>0.2). The results persisted after controlling for sex, the time of the day, and the date when CIT was assessed. Our results suggest that human BAT activity and skeletal muscle 18F-FDG activity are not associated to CIT in young healthy adults. Inherent limitations of the available radiotracers for BAT detection and muscle activity quantification may explain why we failed to detect a physiologically plausible association.